Bidirectional Relationships Between Cyberbystanders' Roles, Cyberbullying Perpetration, and Justification of Violence. Issue 4 (May 2023) - Orue, Izaskun; Fernández-González, Liria; Machimbarrena, Juan M.; González-Cabrera, Joaquin; Calvete, Esther
Bystanders play a key role in understanding the phenomenon of cyberbullying (CB). The main aim of this study is to explore longitudinal bidirectional relationships among cyberbystanders' reaction, CB perpetration, and CB justification. Participants were 1, 105 adolescents (56.7% girls; M age  = 13.56, SD  = 1.21) who answered self-reported questionnaires about CB perpetration, CB justification, and cyberbystanders' reaction at two measurement periods spaced 8 months apart. The results showed that cyberbystanders who assisted and/or reinforced the aggressor had higher scores for CB perpetration and justification than those who supported or defended the victim. Furthermore, cyberbystanders' pro-aggressive behavior at Time 1 (T1) predicted an increase in CB perpetration and justification at Time 2 (T2), and T1 CB perpetration predicted an increase in T2 CB justification. These findings highlight the precursor role that acting as an assistant or reinforcer of the perpetrator may have on their own perpetration of future CB aggressions.